Ni loaded SnS2 hexagonal nanosheets for photocatalytic hydrogen generation via water splitting. Issue 4 (16th January 2023) - Jawale, Niteen; Arbuj, Sudhir; Umarji, Govind; Shinde, Manish; Kale, Bharat; Rane, Sunit
Abstract : Schematic of photocatalytic H2 generation using Ni/SnS2 nanosheets along with the energy levels of SnS2 and Ni nanostructures. Abstract : Herein we have prepared the Ni-decorated SnS2 nanosheets with varying concentrations of Ni from 1 to 10 mol% (1, 2.5, 5, and 10 mol%) and studied their various physicochemical and photocatalytic properties. The chemical reduction technique was utilized to load the Ni nanoparticles on SnS2 nanosheets. The synthesized Ni decorated SnS2 (denoted as Ni-SnS2 ) was characterized using different spectroscopic techniques such as X-ray diffraction, diffuse reflectance UV-vis and photoluminescence spectroscopy, field emission scanning electron microscopy (FESEM), and field emission transmission electron microscopy (FETEM). XRD revealed the formation of the highly crystalline hexagonal phase of SnS2 but for nickel loading there is no additional peak observed. Further, the as-prepared Ni-SnS2 nano-photocatalyst shows absorption behaviour in the visible region, and photoluminescence spectra of the Ni-SnS2 nanostructures show band edge emission centred at 524 nm, and the peak intensity decreases with Ni loading. The FE-SEM and FE-TEM confirm the formation of hexagonal sheets having evenly distributed Ni nanoparticles of size ∼5–10 nm. BET surface area analysis was observed to be enhanced with Ni loading. The photocatalytic performance of the prepared Ni-SnS2 nanosheets was evaluated for hydrogen generation via water splitting under a 400 W mercury vapour lamp. Among the prepared Ni-SnS2 nanostructures, the Ni loaded with 2.5 mol% provided the highest hydrogen production i.e., 1429.2 μmol 0.1 g −1 (% AQE 2.32) in four hours, almost 1.6 times that of pristine SnS2 i.e., 846 μmol 0.1 g −1 . Furthermore, the photocatalytic performance of the catalyst is also correlated with the photoconductivity by measuring the photocurrent. The photoconductivity of the samples is revealed to be stable and the conductivity of 2.5 mol% Ni-SnS2 is higher i.e. 20 times that of other Ni-SnS2 and pristine SnS2 catalysts.